Evaluasi Tingkat Kecukupan Pasokan Air PAMSIMAS Pokmas Tambiliok Jaya Desa Muara Jalai dan Ketepatan Distribusinya Bagi Warga Masyarakat Sekitar - Ardiansyah Hamid; Harmi Yelmi; Ivan Fadhillah; Rezki Putra (Jurnal Rekayasa Proses dan Industri Terapan, 2025)
The Community-Based Drinking Water and Sanitation Program (PAMSIMAS) is one of the government's efforts to improve community access to safe drinking water, especially in rural areas. This study aims to evaluate the adequacy of the PAMSIMAS water supply managed by the Tambiliok Jaya Community Group (Pokmas) in Muara Jalai Village and assess the accuracy of its distribution to the surrounding community. Initial conditions before the program was implemented indicated that some residents only received low-quality water, namely cloudy, brownish-yellow, and oily. The PAMSIMAS program has been operating since 2022, so an evaluation of its performance is necessary after more than two years of implementation. The research method used a qualitative descriptive approach with data collection through field observations and interviews with beneficiaries. The analysis results indicate that the current PAMSIMAS water supply has met the community's daily needs and is considered sufficient and stable over time. Furthermore, service distribution is considered well-targeted because the main beneficiaries are residents who previously experienced water quality problems. These results indicate that the existence of the Tambiliok Jaya Community Group (Pokmas) PAMSIMAS has had a positive impact on better access to safe drinking water for the Muara Jalai Village communit.